Avaliação dos efeitos cardiovasculares induzidos pelo extrato etanólico das folhas da Aspidosperma Macrocarpum Mart. (APOCYNACEAE) em ratos - Oliveira, Manuelle Prestrelo de (2012)
Aspidosperma macrocarpum Mart is a plant popularly known as "mahogany-giant-do-cerrado". Species of the genus Aspidosperma have various pharmacological activities and are used in the treatment of leishmaniasis, inflammation of the uterus and ovary, diabetes, malaria, and fever. Although several studies and significant Aspidosperma species of the genus, some species are scarcely reported or even lack studies of biological activities. An example is the species A. macrocarpum. The objective of this study was to investigate the cardiovascular effects induced by ethanol extract of leaves of A. macrocarpum (EEAM) through an approach in vivo and in vitro. The administration of doses random manner EEAM (1, 5, 10 and 20 mg/kg, i.v.) promoted a transient hypotension (-17 ± 2 -12 ± 2 -12 and -17 ± 1, ± 3 mmHg, respectively) and a bradycardia (-3 ± 1 -10 ± 3, -4 and -5 ± 1 ± 2 bpm, respectively) independently of dose in normotensive rats unanesthetized. The hypotensive response was induced EEAM Significantly attenuated at doses of 10 and 20 mg / kg in the presence of L-NAME, a nonselective inhibitor of NOS synthase, but the bradycardic response was not changed. After blocking with atropine, a nonselective blocker of muscarinic receptors, the hypotensive response was abolished and reversed significantly, since the bradycardia was potentiated. In the superior mesenteric artery rings isolated from normotensive rat, EEAM (0,03-300 μg/ml) induced a concentration-dependent vasorelaxation in rings with endothelium (CE50= 273  6 μg/ml) the effect was not altered after removal of the endothelium(CE50 =117  3 μg/ml). The EEAM induced relaxation in endothelium-free mesenteric rings pre-contracted with 80 mM KCl (CE50= 323  3 μg/mL). The orogastric administration of the extract (200 mg / kg) induced a significant decrease in mean arterial pressure in spontaneously hypertensive rats. In conclusion, these results suggest that promotes EEAM bradycardic and hypotensive effect in normotensive rats unanesthetized. This hypotension is probably due to activation of muscarinic M3-type, resulting vasorelaxation of vascular smooth muscle and also features an antihypertensive effect.